EVALUATION, ANALYSIS AND MODIFICATION OF THE BLANEY-MORIN - NIGERIA (BMN) EVAPOTRANSPIRATION MODEL (Nigerian Journal of Technology, 2003)
The analytical approach of the Blaney-Morin-Nigeria (BMN) evapotranspiration model was applied to data sets obtained from seventeen locations in Nigeria and the values of the constants m and H in the BMN model, Equation 1 were not as consistently comparable as expected. Thereupon, the Standard Difference (SDF) method was applied to each of the seventeen locations (designated as model ETPP4), to each of the five regions formed by pooling data from meteorologically similar locations (ETPP3) and to the pooled data from all locations (ETPP1). The values of m and H thus obtained were consistently comparable and within the range considered acceptable for the country. While the models predict potential evapotranspiration (PET) more accurately than the Penman equation under the Nigerian conditions, their performances are similar to that of the BMN model. However, ETPP4 and ETPP3, produce better prediction in their corresponding locations and regions while ETPPI predicts PET slightly better than the 3MN model at those locations where the BMN model was not originally evaluated. Consequently, the SDF method is recommended as a procedural modification of the development of the BMN model and the most general form of the models, ETPPI (m = .29, H = 508) is recommended as a refinement of the BMN model.